SOSIALISASI MENGENAI KEPATUHAN MINUM OBAT CACING BAGI ANAKANAK SD NEGERI 4 JAMBON KABUPATEN GROBOGAN - Gigih Kenanga Sari; Miki Rofi’atun Masriah; Diyana Wulandari (LPPM AN Nuur, 2023)
Background: Worms are an infectious disease caused by the entry of parasites in the form of worms into the human body. Worm infections can cause public health problems, especially in children who are still in elementary school age. If worms are not treated, they will reduce the child's learning ability and the child's health. Objective: to increase the level of knowledge among students regarding the importance of taking worm medicine regularly, preventing worms in everyday life, and to create children who have more self-aware personalities, so they do not get worms. Method: Socialization and discussion in SD N 4 Jambon class 5. Results: There were 22 students in 1 class who complied with taking worm medicine for students at SD N 4 Jambon. Conclusion: compliance awareness of students taking worm medicine for students at SD N 4 Jambon.